2018
DOI: 10.1584/jpestics.d17-091
|View full text |Cite
|
Sign up to set email alerts
|

<i>m</i>-Coumaric acid attenuates non-catalytic protein glycosylation in the retinas of diabetic rats

Abstract: In this study, we investigated the inhibitory effects of m-coumaric acid on the glycosylation of proteins in the retinas of diabetic rats. Male rats were divided into two main groups, Group I (normal control) and Group II (diabetic); Group II was further divided into four subgroups: Group IIa (diabetic control), Group IIb (diabetic rats were given m-coumaric acid orally [150 mg/kg, body weight (bw)/day]), Group IIc (diabetic rats were given HCA m-coumaric acid orally [300 mg/kg bw/day]), and Group IId (diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The antioxidant properties of shogaol prevented fructose and Amadori products from oxidation, leading to the inhibition of AGEs production. The same result was found in a recent study using pyrogallol ( Zhang et al, 2019 ) and p-Coumaric acid ( Moselhy et al, 2018 ) which showed their antiglycation ability by inhibiting further oxidation of glycated proteins and oxidation of metal-catalyzed glucose which leads to the formation of AGEs. Protein glycation activity can also be inhibited by cinnamic acid ( Adisakwattana et al, 2012 ) using the BSA-fructose method.…”
Section: Discussionsupporting
confidence: 83%
“…The antioxidant properties of shogaol prevented fructose and Amadori products from oxidation, leading to the inhibition of AGEs production. The same result was found in a recent study using pyrogallol ( Zhang et al, 2019 ) and p-Coumaric acid ( Moselhy et al, 2018 ) which showed their antiglycation ability by inhibiting further oxidation of glycated proteins and oxidation of metal-catalyzed glucose which leads to the formation of AGEs. Protein glycation activity can also be inhibited by cinnamic acid ( Adisakwattana et al, 2012 ) using the BSA-fructose method.…”
Section: Discussionsupporting
confidence: 83%
“…Caffeic and coumaric acid both showed a significant decrease (79.2% and 43.6%) respectively at 200 µM concentration (Figure 4A,B). The antiglycative properties of caffeic acid and coumaric acid have been investigated in previous studies [53,54]. AGEs are the key players in the pathophysiology and progression of many diseases highlighting their clinical significance [30].…”
Section: Inhibition Of Advanced Glycation End-products (Ages)mentioning
confidence: 99%
“…Thus, a conclusion was obtained that both the ligands attenuate the effect of MG by networking with HSA and reduce the fluorescence by AGEs. AGEs not only create a menace in diabetes but also contribute to other fatal diseases [29,53], signifying an urgent need to stop AGEs formation [54]. Antiglycation activities of caffeic and coumaric acid could be due to its antioxidant, ROS scavenging activity and protein-stabilizing potential.…”
Section: Inhibition Of Advanced Glycation End-products (Ages)mentioning
confidence: 99%
“…Synirgic acid downregulates altered levels of metabolic enzymes and stimulates β-cells regeneration to prevent pancreatic damage [52]. m-coumaric acid inhibits the overproduction of reactive oxygen species thus suppressing hyperglycemia-induced vascular damage [53]. Hence, in the present study, it can be attributed to the presence of these phytochemicals in Me .…”
Section: Discussionmentioning
confidence: 69%